(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The predatory efficiency of the Old World "hunter fly", Coenosia attenuata, on several species of insect pests justifies its use as a biocontrol agent in greenhouses. The records of Coenosia attenuata from Ecuador and Pem reported here are the first from the Neotropical Region.